Pendampingan dan Psikoedukasi Pengasuhan Anak Autism Spectrum Disorder pada Staff dan Orangtua Dampingan PLA Naimata - Friandry Windisany Thoomaszen; Philia Octavianus; Devi Novita Sheldena; Gusti Sette; Resinta Febriyanti Tade; Omri Boki; Berti Toabnani (Universitas Muhammadiyah Surakarta, 2023)
Due to the numerous challenges of providing for autistic children on a daily basis, parental cluelessness of how to care for autistic children, and lack of parental support for the therapy process that has been taught by the Autism Service Center, parents with autistic children are more likely to experience stress. As a result, employing the PAR methodology, Christian psychology study programs engage in community service projects that teach parenting techniques for raising autistic children. The PKM team engages in mentoring and psychoeducational activities, which are divided into two primary sessions (i.e, Session 1 included lecturing, relaxation, and question and answer; Session 2 including simulation, roleplaying, and question-and-answer). The PKM activity process was examined both quantitatively and qualitatively. With the highest scores in the very good category (74.07%, 59.25%, and 55.55% respectively), participants gave the elements of a comfortable setting or facility, handouts or teaching materials that are very helpful in learning and comprehending the content, and a willingness to join once more if the Christian Psychology Study Program offers another activity. Based on the qualitative data, the participants explicitly expressed their opinion that this activity was very good, useful, could transfer new knowledge in regards to caring for ASD children, could address their needs and difficulties, and it was hoped that this activity would be sustained in the future. Thus, resources and a number of delivery modalities can be used to provide support and psychoeducation about parenting styles for kids with autism, which can address the needs, aspirations, and issues of PLA Naimata Staff and Assisted Parents.